Discovery–dominance trade‐off among widespread invasive ant species. Issue 13 (17th June 2015) - Bertelsmeier, Cleo; Avril, Amaury; Blight, Olivier; Jourdan, Hervé; Courchamp, Franck
Abstract Ants are among the most problematic invasive species. They displace numerous native species, alter ecosystem processes, and can have negative impacts on agriculture and human health. In part, their success might stem from a departure from the discovery–dominance trade‐off that can promote co‐existence in native ant communities, that is, invasive ants are thought to be at the same time behaviorally dominant and faster discoverers of resources, compared to native species. However, it has not yet been tested whether similar asymmetries in behavioral dominance, exploration, and recruitment abilities also exist among invasive species. Here, we establish a dominance hierarchy among four of the most problematic invasive ants (Linepithema humile, Lasius neglectus, Wasmannia auropunctata, Pheidole megacephala) that may be able to arrive and establish in the same areas in the future. To assess behavioral dominance, we used confrontation experiments, testing the aggressiveness in individual and group interactions between all species pairs. In addition, to compare discovery efficiency, we tested the species' capacity to locate a food resource in a maze, and the capacity to recruit nestmates to exploit a food resource. The four species differed greatly in their capacity to discover resources and to recruit nestmates and to dominate the other species. Our results are consistent with a discovery–dominance trade‐off. The species that showed the highest level of interspecific aggressiveness and dominance during dyadic interactions.